ANALYSIS OF STAD AND JIGSAW COOPERATIVE LEARNING : A RECOMMENDATION FOR CLASSROOM PRACTICES - Luwiti, Sri Rumiyatiningsih; Mahmud, Muzdalifah; Panigoro, Fadlia (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2023)
Cooperative learning, especially through Jigsaw and STAD methods, is widely employed to enhance student engagement and academic achievement. This research reviews the effectiveness of implementing Jigsaw and STAD cooperative learning in high school English classrooms in Indonesia. The qualitative approach involves library research, analyzing 40 studies spanning 2013 to the present. Findings indicate that both strategies can be applied to all English skills, with STAD more suited for receptive skills and Jigsaw for productive skills. The flexibility of these strategies allows adaptation to diverse student conditions, learning topics, and objectives. Theoretical benefits include insights into implementing these cooperative learning models, aligning with government initiatives like MBKM and the Merdeka curriculum. Practical benefits include guiding educators and researchers in utilizing these strategies effectively. The research underscores the need for proper application and favorable conditions, emphasizing the importance of resources and educator oversight in cooperative learning success.